Complex Automated Information System for Remote Management of Crisis Situations in Rail Transport - Dvorak, Zdenek; Luskova, Maria; Hruza, Petr; Sousek, Radovan (Communications - Scientific letters of the University of Zilina, 2013)
The paper deals with topical information from the area of crisis information support. The contributing authors work at three co-operating universities where the subject of transport support in crises is tackled. At present the electronic support of crisis management in transport is necessary prerequisite for the functioning of transport system under both common and emergency situations. The outcomes of scientific research projects are new even from a broader European perspective. The preparation of complex automated information system for remote management of crisis situations in rail transport is new and has not been published yet. The outcomes of extensive analysis, gradually developed methodologies and data sets are presented in the paper together with the current outcomes regarding the electronic support of crisis management in transport.